Can a Trial of Motivational Lifestyle Counseling be Effective for Controlling Childhood Obesity and the Associated Cardiometabolic Risk Factors? - Roya Kelishadi; Mohammad Malekahmadi; Mahin Hashemipour; Mehrnaz Soghrati; Mojgan Soghrati; Parisa Mirmoghtadaee; Shohreh Ghatrehsamani; Parinaz Poursafa; Noushin Khavarian (Pediatrics and Neonatology)
This study was conducted to assess the effectiveness of a simple office-based program for encouraging healthy lifestyle on controlling childhood obesity and associated cardiometabolic risk factors. Methods: This non-randomized 24-week lifestyle modification trial was conducted among 457 obese children and adolescents, aged 2–18 years, who had at least one cardiometabolic risk factor in addition to obesity. This trial included three components of exercise, diet education and behavior modification, with all recommendations provided by a pediatrician, two general physicians and a nurse. Instead of strict inhibitory recommendations, healthier lifestyle was encouraged. Results: Overall 448 (98.04%) of enrolled children completed the trial with a mean age of 9.6 ± 2.9 years. After the trial, the mean of anthropometric measures and cardiometabolic risk factors decreased significantly, the mean high-density lipoprotein cholesterol (HDL-C) increased significantly, and the prevalence of the metabolic syndrome decreased from 20.8% to 1.8%. Triglycerides, LDL-C, diastolic blood pressure and WC had the highest decrease in all age groups, with the most prominent changes in the 14–18-year age group. By each -1SD decline in BMI and WC, risk factors had significant improvement. Conclusion: Motivational office-based counseling can be effective in treatment of childhood obesity and its associated cardio-metabolic risk factors. Such approach can be implemented in the primary health care system; and can be of special concern in low- and middle-income countries with limited human and financial resources. We suggest that expanding the roles of non-physician clinicians such as nurse practitioners can help to increase the amount of time available for such services.